Skin mucus from cachama blanca (Piaractus orinoquensis) as a low-invasive method to assess welfare in fish (2023)
Skin mucus contributes to the ﬁsh defense against the surrounding environment and reﬂects the state of health of the ﬁsh; therefore, it is a low-invasive and non-lethal matrix appropriate to assess welfare. However, more information is required on the response to stressors in Latin America ﬁsh species. At this regard, in Colombia the most important native ﬁsh species used in aquaculture is cachama blanca (Piaractus orinoquensis) begin necessary to depth in their physiological knowledge. Therefore, this study compared the skin mucus as another study matrix in ﬁsh exposed to low concentrations of dissolved oxygen in the water as stress factor. This study was carried out in P. orinoquensis specimens subjected to several intervals of hypoxic conditions and subsequently sampled after 0, 2, 4, 6, 24, 48 and 72 h of repetitive poststress condition. Skin mucus and plasma were collected and a battery of biochemical biomarkers were measured in both matrices. The analysis showed signiﬁcant shifts of indicators such as glucose activity, protein concentration and lactate activity being signiﬁcantly higher in skin mucus than in plasma compared to control and also having a highest response at 6, 24, 48 and 72 h post-stress; however, only signiﬁcant variations were found in plasma cortisol levels at 4, 6 and 24 hours compared to the control. These results demonstrate that skin mucus in P. orinoquensis can be used as non-invasive matrix for stress assessment in ﬁsh, since several biomarkers presented a similar pattern of response in the skin mucus, becoming an appropriate matrix to evaluate either health of ﬁsh and aquatic systems. Acknowledgment: This study was funded by the Universidad de los Llanos, project number C09-F01-001 2020 "Evaluación del potencial del mucus de la piel de cachama blanca (P. brachypomus) como un método no invasivo y conﬁable para evaluar el bienestar de los peces a través de pruebas bioquímicas".